A Fusion of Educational Research and Fuzzy Information: A Pragmatic Approach - Naeem Butt, Muhammad; Shafiq, Muhammad (The Journal of Humanities & Social Sciences, 2022)
Results and recommendations, based on data interpretation, in the research of social sciences are generated on precise measurements. However, advancement of numerical sciences showcases the unattainability of precise measurement of continuous phenomena due to the recent conception of fuzziness. Measurement results establish through educational research are obtained mostly by employing classroom experiments, survey-questionnaires and/or standardized-questionnaire; whereas, available literature also suggests the occurrence of fuzziness in classical measurement and questionnaire responses instead of preciseness. Therefore, in educational research it is recommended to employ latest measurement technique, i.e. fuzzy numbers instead of precise numbers, which will authenticate the reliability and appropriateness of obtained results.